Analisis Respon Penawaran Pisang di Provinsi Bali - WIWAHA, FREDERICK GERALDI; WIDHIANTHINI, WIDHIANTHINI; SUKENDAR, NI MADE CLASSIA (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.11, No.2, Desember 2022, 2022)
Analysis of Banana Supply Response in Bali Province Banana is classified as horticultural plant that can grow well in Indonesia because the soil and climate are suitable for its growth. The research objectives were to analyse the factors that influenced the banana supply response in Bali Province and to analyse the elasticity of banana supply in Bali Province. This research was conducted in Bali Province. Determination of the research area with a purposive method secondary data is in the form of time series data for 10 years from 2010 to 2019. Types of data used include banana production data, harvested area data, banana prices, and competitor commodity prices. Analysis using multiple linear regression models. The results of this study indicate 1) The multiple linear regression model of banana supply in Bali Province is declared feasible in the classic assumption test of multicollinearity, autocorrelation, and heteroscedasticity. 2) The value of R 2  adjusted is 0.887 which means that 88.7% is influential, the calculated F value is greater than the F table value. The t test analysis results show that only the banana production variable in the previous year has no effect. 3) The short-term and long-term elasticity values ??for banana prices are -0.2498 and -0.4143, Banana harvest area is 0.7909 and 1.3117, and the mango price is 0.5376 and 0.8916. Suggestions for the government to help make policies related to banana supply in Bali increase.